Case Study: Implementation of Electronic Tilang in School Environment and Its Impact on Students - Candra Tangoi; Syahhruddin Hattab; Mustainah (Jurnal Penelitian Pendidikan IPA, 2024)
Implementing electronic ticketing in the school environment aims to improve driving discipline and student traffic safety. This case study reveals that implementing e-ticketing effectively reduces traffic violations and enhances compliance with rules. In addition, this program also plays a role in driving safety education. However, there are challenges in the form of psychological impact on students who feel pressured by close supervision. With the proper psychological and educational support, these negative impacts can be minimized so that the main objectives of this program can be achieved.